Heat transfer characteristics of a gas cooler. (September 2019) - Dima, D; Bucsa, S; Ionita, C; Vasilescu, E E; Dobrovicescu, A; Niculae, E
Abstract: The paper deals with the design and simulation of a gas-water heat exchanger used for heating purposes. The heat exchanger represents the gas-cooler/water heater of a transcritical CO2 heat pump. The log-mean temperature difference and the NTU-ε methods are comparatively analyzed. The heat transfer area can be calculated through both methods but the true strength and what makes the difference when using the NTU-ε method is that based on it the simulation of the behaviour of an existing heat exchanger can be easily performed.